Respuesta :
Answer:
4(x+2)(x-2)
Step-by-step explanation:
4x^2-16
4(x^2-4)
4(x+2)(x-2)
The difference of two squares formula is (a+b)(a-b), and it happens only when a^2 is minus b^2
So, 4x^2 − 16 = (2x + 4)(2x − 4).
Explanation:
4x2^ − 16 is of the form a^2 − b^2 (where a = 2x, b = 4), and as per the identity:
a^2 − b^2 = (a + b)(a − b)
So, 4x^2 − 16 = (2x + 4)(2x − 4)
Explanation:
4x2^ − 16 is of the form a^2 − b^2 (where a = 2x, b = 4), and as per the identity:
a^2 − b^2 = (a + b)(a − b)
So, 4x^2 − 16 = (2x + 4)(2x − 4)